Evaluation of the power of a savonius prototype aerogenerator type - de Matos, Lucas (2017)
The objective of this article is to construct a prototype of a wind turbines with vertical axis type Savonius us-ing materials that are easily accessible and available on the market. Due to the increase in energy demand in Brazil, other sources have been sought for the genera-tion of energy, especially renewable sources since there is an increasing concern for the environment and the attempt to mitigate gas emissions of fossil origin. Wind energy in Brazil has presented an excellent alternative of electric power generation due to the high potential of wind efficiency. The present work aims to construct a prototype of wind turbines of a vertical axis of the type Savonius using materials of easy access and available in the market aiming a low cost in the construction of the same one. Savonius vertical axis aerogenerators are known to be simple, both in terms of construction and operation. They have the power conversion devices at the base of the wind turbine, in which it facilitates the operations of possible maintenance. In addition, in this turbine model no turbine orientation devices are re-quired, but since they are low-height wind turbines, they have lower yields due to the quality of the winds near the ground. In this project, the prototype is being as-sembled with ¾-inch diameter steel tubes and a struc-ture of approximately 1.3 meters, and the blades were constructed using 1 millimeter-thick aluminum. The structure is being designed in such a way that the tur-bine can be easily moved so that it is possible to per-form tests in several places aiming the behavior in dif-ferent types of wind. The connection of the wind turbine to the generator will be made by pulleys of different sizes interconnected by a belt. In addition, the project will use a low-cost generator, where it will be possible to draw the data through a multimeter. The project aims to evaluate the power of the prototype of the aerogener-ator in different environments aiming at a low cost in construction.